Modeling and simulation of social-behavioral phenomena in creative societies : first International EURO Mini Conference, MSBC 2019, Vilnius, Lithuania, September 18-20, 2019, proceedings /: first International EURO Mini Conference, MSBC 2019, Vilnius, Lithuania, September 18-20, 2019, proceedings. ([2019]) - Unknown
No abstract available